In vivo whole brain, cellular and molecular imaging in nonhuman primate models of neuropathology. (July 2016) - Huang, Lieven; Merson, Tobias D.; Bourne, James A.
Graphical abstract: Abstract: Rodents have been the principal model to study brain anatomy and function due to their well-mapped brain architecture, rapid reproduction and amenability to genetic modification. However, there are clear limitations, for example their simpler neocortex, necessitating the need to adopt a model that is closer to humans in order to understand human cognition and brain conditions. Nonhuman primates (NHPs) are ideally suited as they are our closest relatives in the animal kingdom but in vivo imaging technologies to study brain structure and function in these species can be challenging. With the surge in NHP research in recent years, scientists have begun adapting imaging technologies, such as two-photon microscopy, for these species. Here we review the various NHP models that exist as well as their use in advanced microscopic and mesoscopic studies. We discuss the challenges in the field and investigate the opportunities that lie ahead.